Notarella su Merito e Competenze nell’attuale risveglio, anche pedagogico, dell’Unione Europea - Franco Cambi (Studi sulla Formazione, 2022)
Due to the current war in Ukraine, the E.U. must decisively rethink its values and educational models: it is necessary to develop them on the economic and socio-political levels, putting the principle of democratic citizenship at the center.